Fifteen-minute consultation: Obvious and not-so-obvious mediastinal masses. Issue 6 (2nd May 2019) - Green, Katherine; Behjati, Sam; Cheng, Danny
Abstract : Objectives: To present a structured approach to the management of a child with a mediastinal mass presenting to the emergency department. To raise awareness of presenting features of less-obvious mediastinal masses and to encourage consideration of mediastinal masses in differential diagnoses. Methods: Review of the relevant literature and review of London Paediatric Cancer Network supportive guidelines and subsequent description of the approach to a child presenting with features suggestive of a mediastinal mass. Conclusions: A systematic approach to history taking, clinical examination and investigation of a child presenting with a mediastinal mass will assist in the safe and timely management of children presenting when they are critically unwell. Anticipation of potential management complications and early transfer for ongoing management will improve patient outcomes and minimise morbidity.